Resistance profile of osimertinib in pre-treated patients with EGFR T790M-mutated non-small cell lung cancer - Fernandes, Maria Gabriela O. (2021)
Osimertinib efficacy in pre-treated patients with epidermal growth factor receptor (EGFR) T790M-mutated non-small cell lung cancer (NSCLC) has been demonstrated in clinical trials, but real-world data, particularly regarding resistance profile, remains limited. This study aims to analyze the resistance mechanisms acquired after treatment with Osimertinib. Clinical outcomes and molecular results from re-biopsies at the time of osimertinib progression of EGFR T790M-mutated NSCLC patient were analyzed. Twenty-one patients with stage IV adenocarcinoma were included [median 69 years; 57.1% female; 85.7% never-smokers; 23.8% ECOG performance status (PS) ≥2]. Median PFS and OS were 13.4 (95% CI: 8.0–18.9) and 26.4 (95% IC: 8.9–43.8) months, respectively. At the time of analysis, 10 patients had tumor progression (47.6%). T790M loss occurred in 50%, being associated with earlier progression (median PFS 8.1 vs. 21.4 months, p = 0.011). Diverse molecular alterations were identified, including C797S mutation (n = 1), PIK3CA mutation (n = 2), MET amplification (n = 1), CTNNB1 mutation (n = 1), and DCTN1-ALK fusion (n = 1). Histological transformation into small cell carcinoma occurred in one patient. This real-world life study highlights the relevance of re-biopsy at the time of disease progression, contributing to understand resistance mechanisms and to guide treatment strategies.